‘Without uniform I am a community member, uncle, brother, granddad’: Community policing in Australia’s Torres Strait Region - Staines, Zoe (Journal of criminology, 2021)
As a palpable legacy of violent colonialism, Aboriginal and Torres Strait Islander (?Indigenous?) Australians are the most incarcerated peoples in the world. Community policing, which hinges on the development of trusting community?police partnerships, is frequently proposed as a means of reducing this over-representation, but approaches vary and produce divergent outcomes. This article draws on interview data to explore policing in Australia?s Torres Strait Region ? a remote archipelago situated off the northern tip of Queensland. A strong commitment to community and hybridised policing approaches likely provide a partial explanation for relatively low crime in the region. However, under-reporting of some offences (e.g. domestic violence) suggests a possible need to overlay alternative approaches that improve access to justice for all victims, especially women. Overall, the Torres Strait Region experience holds possible lessons for policing in Australia?s other remote Indigenous communities, again demonstrating that decolonisation is a critical starting point for addressing over-representation.